HYDRUS-2D simulations of water movement in a drip irrigation system under soilless substrate - Geng, Lei; Li, Li; Li, Wei; Yang, Chengfei; Meng, Fanjia (International Journal of Agricultural and Biological Engineering, 2022)
A comprehensive understanding of the distribution and water movement of the substrate in root areas is crucial to the design and management of drip irrigation systems, which is a significant step to maximizing crop water use efficiency by understanding the hydrodynamics in soilless substrates. In this study, an improved HYDRUS-2D model by the dynamic root growth model was used to simulate water movement under the condition of drip irrigation and the water uptake process of the root, and then, compared with the observed data. Substrate water content under drip irrigation was also measured with the calibrated ECH20-EC5 sensors. The situation of substrate water movement was analyzed under the conditions of different depths, different initial water content, and different irrigation amount. The substrate water movement under different drip irrigation conditions was explored. The results showed that incorporating the defined initial and boundary conditions and the hydraulic characteristics of the substrate into the model enabled HYDRUS model to predict the movement and position of water in unsaturated porous media by solving Richards equation. Under drip irrigation, the substrate wetting body was approximately a quarter ellipse, and the water would continue to move to the area where the wetting front did not reach within 1 h after irrigation. The simulation results of the improved HYDRUS-2D model agreed well with those observed by the ECH2O-EC5 sensors, and the model could provide a basis for precision irrigation of soilless substrate culture under drip irrigation. Keywords: drip irrigation, HYDRUS-2D, substrate water movement, soilless substrate DOI: 10.25165/j.ijabe.20221503.6951 Citation: Geng L, Li L, Li W, Yang C F, Meng F J. HYDRUS-2D simulations of water movement in a drip irrigation system under soilless substrate. Int J Agric & Biol Eng, 2022; 15(3): 210–216.